2020
DOI: 10.3389/fpubh.2020.00021
|View full text |Cite
|
Sign up to set email alerts
|

Mental and Physical Health Correlates of Financial Difficulties Among African-American Older Adults in Low-Income Areas of Los Angeles

Abstract: Background: While financial difficulties correlate with mental and physical health status, less is known about these associations among economically disadvantaged African-American (AA) older adults. Objective: This study explored mental and physical health correlates of financial difficulties among AA older adults in low-income areas of south Los Angeles. Methods: A cross-sectional study on 740 AA older adults (age ≥ 55 years) conducted in South Los Angeles between 2015 and 2018. Independent variable was finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Socioeconomic support cannot play a role in the self-rated health of the elderly patients with chronic diseases in the central regions, but significantly improve the health status of the elderly patients with chronic diseases in the western regions. Evans, MC study finds that economic difficulties have an impact on the health of low-income elderly persons and suggested that solving economic difficulties may help to promote the health of the elderly (50). The interpretation of this paper is that in undeveloped regions, the family economic condition cannot meet the normal health needs of elderly patients with chronic diseases, thus, worsening the health status of the elderly.…”
Section: Discussionmentioning
confidence: 83%
“…Socioeconomic support cannot play a role in the self-rated health of the elderly patients with chronic diseases in the central regions, but significantly improve the health status of the elderly patients with chronic diseases in the western regions. Evans, MC study finds that economic difficulties have an impact on the health of low-income elderly persons and suggested that solving economic difficulties may help to promote the health of the elderly (50). The interpretation of this paper is that in undeveloped regions, the family economic condition cannot meet the normal health needs of elderly patients with chronic diseases, thus, worsening the health status of the elderly.…”
Section: Discussionmentioning
confidence: 83%
“…This community-based cross-sectional study surveyed a convenience sample (n = 740) of older African Americans residing in South Los Angeles [3,4,6,[28][29][30][31]. Also referred to as "South Los Angeles" Service Planning Area 6 of Los Angeles County, which serves the communities of Athens, Compton, Crenshaw, Florence, Hyde Park, Lynwood, Paramount, and Watts.…”
Section: Methodsmentioning
confidence: 99%
“…This subset of older adults is faced with numerous health disparities, including lower rates of preventative health services and a greater delay in care. Individuals enrolled in any type of nursing facility, enrolled in any other research study, and who have observable intellectual impairments, were excluded from this study [3,4,6,[28][29][30][31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study 57 , economic strain was positively associated with chronic diseases, chronic pain, self-rated health, depressive symptoms, and sick days. Although this study suggested that economic strain seems to be linked to self-rated health, sick days, chronic pain, chronic diseases, and depressive symptoms, this study did not compare the role of economic strain and educational attainment.…”
Section: Introductionmentioning
confidence: 93%